Functional Characteristics of a Protective Monoclonal Antibody against Serotype A and C Lipooligosaccharides from Moraxella catarrhalis - Hu, Wei-Gang (American Society for Microbiology, 2001)
A monoclonal antibody (MAb), designated MAb 8E7 (immunoglobulin G3), specific for Moraxella catarrhalis lipooligosaccharide (LOS) was evaluated for its functional activity in vitro and in a mouse model of colonization. Enzyme-linked immunosorbent assay (ELISA) demonstrated that the MAb 8E7 could be prepared to a high titer against LOS of the homologous strain 035E, and that it had bactericidal activity. MAb 8E7 reacted with M. catarrhalis serotype A and C LOSs but not serotype B LOS, as measured by ELISA and Western blotting. On the basis of published structures of LOSs, this suggests that the epitope recognized by MAb 8E7 is directed to a common sequence of either α-GlcNAc-(1→2)-β-Glc-(1→ at the branch substituting position 4 of the trisubstituted Glc residue or a terminal tetrasaccharide α-Gal-(1→4)-β-Gal-(1→4)-α-Glc-(1→2)-β-Glc-(1→ at the branch substituting position 6 of the trisubstituted Glc residue. In a whole-cell ELISA, MAb 8E7 reacted with 70% of the 30 wild-type strains and clinical isolates tested. Immuno-electron microscopy demonstrated that MAb 8E7 reacted with a cell surface-exposed epitope of LOS on strain O35E. MAb 8E7 inhibited the adherence of strain O35E to Chang conjunctival epithelial cells by 90%. Passive immunization with MAb 8E7 could significantly enhance the clearance of strain O35E from mouse lungs in an aerosol challenge mouse model. This enhanced bacterial clearance was inhibited when MAb 8E7 was absorbed by M. catarrhalis serotype A LOS, indicating that the M. catarrhalis LOS-directed antibody may play a major role in the enhancement of M. catarrhalis clearance from lungs. These data suggest that MAb 8E7, which recognizes surface-exposed LOS of M. catarrhalis, is a protective antibody against M. catarrhalis.